On the analytic extension of the Horn's hypergeometric function $H_4$ - Dmytryshyn, R.; Lutsiv, I.-A.; Dmytryshyn, M. (Carpathian Mathematical Publications, 2024)
The paper establishes new convergence domains of branched continued fraction expansions of Horn's hypergeometric function $H_4$ with real and complex parameters. These domains enabled the PC method to establish the analytical extension of analytical functions to their expansions in the studied domains of convergence. A few examples are provided at the end to illustrate this.